Photochemistry of the α-Al2O3-PETN Interface - Roman Tsyshevsky (1652650) (2016)
Optical absorption measurements are combined with electronic structure calculations to explore photochemistry of an α-Al2O3-PETN interface formed by a nitroester (pentaerythritol tetranitrate, PETN, C5H8N4O12) and a wide band gap aluminum oxide (α-Al2O3) substrate. The first principles modeling is used to deconstruct and interpret the α-Al2O3-PETN absorption spectrum that has distinct peaks attributed to surface F0-centers and surface—PETN transitions. We predict the low energy α-Al2O3 F0-center—PETN transition, producing the excited triplet state, and α-Al2O3 F0-center—PETN charge transfer, generating the PETN anion radical. This implies that irradiation by commonly used lasers can easily initiate photodecomposition of both excited and charged PETN at the interface. The feasible mechanism of the photodecomposition is proposed. Other Information Published in: Molecules License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/molecules21030289